KONSTRUKSI MENDUKUNG DAN MENGKRITISI REALITAS PRABOWO SUBIANTO MENJADI MENTERI PERTAHANAN OLEH BEBERAPA MEDIA ONLINE - Sukarno, Sukarno; Amurwani, Pipiet Palestin (Sunan Kalijaga State Islamic University Yogyakarta, 2019)
As the only political opponent in the 2019 presidential election, Prabowo Subianto (PS) became the public spotlight after the election and the inauguration of Jokowi as the President of the Republic of Indonesia. This study aims to reveal how the inauguration of PS as the defense minister in the Kabinet Indonesia Maju (the second period of Jokowi’s cabinet) is framed on Indonesian online media. The data were taken from online media texts that contain supports and criticism that surround this political reality. The data are analyzed descriptively and critically using Fairclough’s critical discouse analysis in order to see how language (vocabulary, modality, grammar, and the choice of media sources) is used in the construction of perspectives and attitudes towards the political news by online mass media. The findings of this research show that there are two types of framing constructed by the online media on PS: support and criticism. In terms of support, it is apparent through the claims that PS is the person that the country needs (President Jokowi), while in terms of criticism, PS is framed as the person who approaches Jokowi for the political position. In addition, the study also reveals that the different framing is highly influenced by the media owner’s alignment towards his own corporation, the market orientation, and the sosiopolitical situations in Indonesia.